1997
DOI: 10.1079/bjn19970134
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing fatty acids in meat and the role of antioxidants in improving meat quality

Abstract: Meat has been identified, often wrongly, as a food having a high fat content and an undesirable balance of fatty acids. In fact lean meat is very low in fat (20-50g/kg), pork and poultry have a favourable balance between polyunsaturated and saturated fatty acids (P : S) and grazing ruminants produce muscle with a desirable n-6:n-3 polyunsaturated fatty acid ratio. In all species, meat fatty acid composition can be changed via the diet, more easily in single-stomached pigs and poultry where the linoleic, a-lino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
301
3
9

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(338 citation statements)
references
References 31 publications
19
301
3
9
Order By: Relevance
“…One possible way to achieve an acceptable balance ratio in beef is to supplement animal diets with natural sources of n-3 FA, specially 18:3 n-3, which is the most predominant FA in grass lipids (Wood and Enser, 1997). Our results clearly showed that calves raised on pasture (P) presented healthy lower values (P , 0.001) for n-6:n-3 ratio than calves finishing on either a long or short concentrate-based period (C or PC, respectively).…”
Section: Pufamentioning
confidence: 99%
“…One possible way to achieve an acceptable balance ratio in beef is to supplement animal diets with natural sources of n-3 FA, specially 18:3 n-3, which is the most predominant FA in grass lipids (Wood and Enser, 1997). Our results clearly showed that calves raised on pasture (P) presented healthy lower values (P , 0.001) for n-6:n-3 ratio than calves finishing on either a long or short concentrate-based period (C or PC, respectively).…”
Section: Pufamentioning
confidence: 99%
“…In addition, the oxidative stability and shelf life of meat depend on the balance between certain FA (such as PUFA), pro-oxidants and antioxidants (Wood and Enser, 1997;Bou et al, 2009) and therefore can be also altered by the modification of the FA composition. Antioxidant vitamins, such as a-tocopherol (aT) and other tocols, contribute to decrease meat oxidability.…”
Section: Introductionmentioning
confidence: 99%
“…This finding has not been previously reported in the literature in which effects of diseases or of specific antioxidants such as vitamin E, vitamin C, plant extracts tested on humans and/or animals were related (Liu et al, 1995;Fano et al, 2001;Alia et al, 2003, etc.). In ruminants, the effects of various antioxidants and especially vitamin E, a liposoluble antioxidant, have been tested in animals fed diets enriched in unsaturated lipids (for review, see Liu et al, 1995;Wood and Enser, 1997;Wood et al, 2003;Durand et al, 2005).…”
Section: Resultsmentioning
confidence: 99%